A low normal force contact using photolithography and Ni-Co electro fine forming technology - Bhuiyan, Moinul; Takemasa, Eiichiro (2009)
This new technology is realized by Photo Resist Lithography and Ni-Co Electro Fine Forming technology, and enables the design of a small contact spring for applications requiring high density, high speed and high durability. The evaluation result proved the capability of Low Normal Force (0.10N-0.15N at 0.3mm) at contact point (5μm radius), durability of 100,000 contact cycles (less than 50m). The particle size of the Ni-Co crystal must be less than 100nm as measured by STEM.